Village of Mazomanie comprehensive planning public opinion survey report - Janke, James; Hadley, Shelly; Trechter, David; Parks, Denise; Gunter, Ramona (My University, 2008)
The purpose for this study was to gather opinions of residents about the future direction of development in the Village of Mazomanie. The survey serves as a key component of the public participation portion of the comprehensive plan for the Village.
35 p.
Keywords: Survey; University of Wisconsin-River Falls. Survey Research Center; UWRF Survey Research Center Report; Public opinion survey; Community planning; Comprehensive plan report; Comprehensive plan; Village of Mazomanie comprehensive plan; Dane County, Wisconsin; Dane County (Wis.); Village of Mazomanie; Mazomanie (Wis. : Village); Mazomanie (Wis. : Village)--Surveys; Public opinion--Wisconsin--Mazomanie (Village); Land use--Wisconsin--Mazomanie (Village); City planning--Wisconsin--Mazomanie (Village)